Mother-Daughter Relationship and Self-Esteem Levels in Undergraduate Midwifery Students at Brawijaya University - Prasanti, Gayatri Anindya; Ariani, Dewi; Maharani, Afniari; Wardani, Diadjeng Setya (Rifa'Institute, 2026)
Introduction: Self-esteem plays an important role in mental health and personal development. However, limited evidence is available regarding the relationship between mother–daughter relationships and self-esteem among midwifery students, particularly in the Indonesian context. Objective: This study aims to examine the association between mother-daughter relationship and self-esteem among undergraduate midwifery students at Brawijaya University. Method: with a cross-sectional. A total of 174 female students were selected from cohorts 2022–2024. The Mother-Adult Daughter Questionnaire (MADQ) was used to assess mother-daughter relationship and the Rosenberg Self-Esteem Scale (RSES) was used to measure self-esteem. Data were analyzed using Spearman rank correlation and ordinal logistic regression. This study employed an observational analytical design. Results and Discussion: Most respondents had high self-esteem and strong mother-daughter relationships. All three dimensions connectedness (r 0.386; p < 0.05;), interdependency dimension has a significant relationship with self-esteem (p < r 0.189; p<0.05), and the trust in hierarchy (; r 0.278 ; p < 0.05) were significantly associated with self-esteem. In multivariate analysis, only connectedness remained a significant predictor. Conclusion: Mother-daughter relationship are significantly associated with self-esteem among midwifery students, with emotional connectedness emerging as the most influential factor. These findings highlight the importance of supportive family relationships in promoting students’ psychological well-being